THE CONCEPT OF “CIVIL DEFENSE (PROTECTION)” IN THE SYSTEM OF PUBLIC GOVERNANCE AS A COMPOSITION PUBLIC SECURITY - Mahortov, P. (Pressing Problems of Public Administration, 2019)
The article analyzes the problems of the conceptual apparatus in the field of civil defense (protection) of the population in emergency situations. The laws of the post-Soviet states, which define the concept of “civil defense (defense)”, are analyzed. The need for elaboration of a unified strategy of public administration bodies for ensuring public safety in the context of protection (defense) of the population against emergencies was emphasized. In recent decades, the attention of the scientific community to problems related to the national security of the state has intensified. Scientists in various fields of the humanities are actively engaged in questions about the role of the state associated with the civil protection of the population in emergency situations. Thus, the work of P. Gaman, S. Dombrovska, V. Emelyanov, L. Zhukov, O. Ostroverkh, S. Pirozhkov, A. Romin, V. Sadkovyi, G. Sytnik, O. Trush and other authors were devoted to various aspects of this issue. At the same time, in our opinion, there is a certain scientific vacuum in determining the categorical base of these issues. So, there is no consensus on the issue of determining the main category of civil defense or civil defense. Different authors have different scientific approaches and interpretations of these concepts. All this makes researchers again and again turn to this issue. The article analyzes various scientific approaches to the definition of the concept of “civil defense” as a factor in ensuring national security, its relationship with the concept of “civil defense” in emergency situations, the role of the public administration system in the issues under consideration. The concept of civil defense (protection) is defined as a state function aimed at protecting the population, territories, natural environment and property from emergency situations by preventing such situations, eliminating their consequences and providing assistance to victims in peacetime and in a special period. Some authors interpret this concept as an integral part of the system of national defense measures carried out in peacetime and wartime in order to protect civilians and national economic objects from the dangers arising from military operations, as well as to carry out rescue and urgent emergency recovery work in areas of catastrophic disaster “ nevertheless, the system of measures in this definition was unjustifiably narrowed only to the defense. Based on the public-managerial nature of activities in the field of civil defense (defense) and taking into account the results of a comparative legal study of the civil defense legislation of the post-Soviet states, it is proposed to specify the concept of “civil defense (defense)” as a system of state measures for the protection of the population established by applicable law, economics of the management system, territory, material and cultural values of Ukraine, ensuring public order in emergency situations of natural, man-made or otherwise, as well as in the event of hostilities.